2000
DOI: 10.1111/j.1151-2916.2000.tb01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hardening of Cement by the Addition of a Mechanically Activated Al(OH)3–Ca(OH)2 Mixture

Abstract: Rapid hardening of cement was achieved in the present study by adding a mechanically activated Al(OH) 3 -Ca(OH) 2 mixture to the starting cement paste. Among the dominant parameters for hardening were the mechanical treatment time for the Al(OH) 3 powder and the Al(OH) 3 /Ca(OH) 2 ratio. The hardening mechanisms are discussed here in terms of the ionic concentration of the solution and the hydration products created when the Al(OH) 3 -Ca(OH) 2 mixture was added to water. Mechanical activation of the Al(OH) 3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The influence of small additions of MgO and Ca(OH) 2 to the oxygen carriers were also investigated. The inclusion of MgO has earlier been found to have beneficial effects on the methane conversion, , and Ca(OH) 2 is a well-known additive to increase the mechanical strength of materials, such as cement . Further, Johansson et al have reported an increased strength when CaO was added to NiO particles supported by NiAl 2 O 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The influence of small additions of MgO and Ca(OH) 2 to the oxygen carriers were also investigated. The inclusion of MgO has earlier been found to have beneficial effects on the methane conversion, , and Ca(OH) 2 is a well-known additive to increase the mechanical strength of materials, such as cement . Further, Johansson et al have reported an increased strength when CaO was added to NiO particles supported by NiAl 2 O 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In the control group, its pH value was increased to 7.53 with transferring the water into reactors, which might be caused by the volatilization of acidic components, and then uctuated around 7.51 (± 0.54) with the depletion of acidic components. However, the pH value of the eco-concrete group was signi cantly increased and maintained to 8.89, which might be caused by the release of Ca(OH) 2 and Al(OH) 3 from calcium sulphoaluminate cement (Kitamura et al, 2000) and the increase of alkalinity resulting from denitri cation (Xing et al, 2018).…”
Section: Effect Of Econ-concrete On Black-odorous Water Remediationmentioning
confidence: 98%
“…Moreover, with the participation of ecoN-concrete, lots of dissolved compounds (such as dissolved organic matters, S 2− , Fe 2+ ) were absorbed by the concrete rapidly (Xie et al, 2021). Simultaneously, the micro-occulation and coprecipitation effect of Ca 2+ , Ca(OH) 2 , and Al(OH) 3 released from the eco-concrete quickly removed the suspended colloids and particles (such as insoluble organic matters, suspended solids), which was the main reasons for turbidity in the black-odorous water (Kitamura et al, 2000). Therefore, a signi cantly decrease of COD and turbidity at the early stage of experiment were observed (Fig.…”
Section: Effect Of Econ-concrete On Black-odorous Water Remediationmentioning
confidence: 99%
“…I NTENSIVE investigations on mechanochemical phenomena have revealed a wide range of mechanochemical reactions, especially during high-energy dry milling, covering almost all the aspects of chemistry [1][2][3][4][5][6][7][8][9][10] and the interests in this field tend to rise continuously, considering the increasing number of the related papers published annually. Based on our efforts, 11,12 it has been found that the mechanochemical reactions depend on the crystal structures of starting materials and the starting materials which easily undergo polymorphous transformation from loose packing to close one of atoms seem to have high reactivity.…”
Section: Introductionmentioning
confidence: 99%